Understanding customers complaint behavior for effective resolution - Nina Angelovska (UTMS Journal of Economics, 2021)
Effective customer complaint management is key for building long-lasting profitable relationships and customer retention. The focus in this study is to investigate the complaints and categorize customer complaint behavior to find the most effective way of compensation for every complaint resolution. Content analysis was conducted on a sample of 220 complaints collected from group buying site, Grouper along with their respective resolutions. The analysed complaints were addressed via e-mail in the period between December 27, 2012 and February 17, 2015. Each complaint was categorized according to the customers' way of expression, along with his/hers expected solution. The analysis showed that based on the way of expression, there are polite and aggressive complainers. Based on the excepted solution three types of inquiries were detected: refund for dissatisfaction; expectation for solution; and complainers that did not expect something in return. The offered complaint resolutions were analyzed and accordingly answers for effective complaint management were provided for each type of complainer. The complaint resolution analyzed in this study resulted in 80% retention, i.e. 80% out of the customers that submitted complaints continued to use Grouper' online services after the expressed dissatisfaction. Given the findings, several recommendations to practitioners and academicians were provided.
Keywords: M30; 330; Complaint management; Online business; Types of complainers; Grouper; North Macedonia